2015
DOI: 10.1128/jvi.02527-14
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid Protein from Fig Mosaic Virus Forms Cytoplasmic Agglomerates That Are Hauled by Endoplasmic Reticulum Streaming

Abstract: Although many studies have demonstrated intracellular movement of viral proteins or viral replication complexes, little is known about the mechanisms of their motility. In this study, we analyzed the localization and motility of the nucleocapsid protein (NP) of Fig mosaic virus (FMV), a negative-strand RNA virus belonging to the recently established genus Emaravirus. Electron microscopy of FMV-infected cells using immunogold labeling showed that NPs formed cytoplasmic agglomerates that were predominantly envel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…If NSm trafficks along the ER membranes, disruption of the ER network should negatively affect this trafficking. We thus tested the effect of brefeldin A (BFA), a pharmacological drug that at high concentrations can disrupt the integrity of the ER network [ 79 , 80 ], on the structural integrity of the ER network in N . benthamiana leaves expressing mCherry-HDEL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If NSm trafficks along the ER membranes, disruption of the ER network should negatively affect this trafficking. We thus tested the effect of brefeldin A (BFA), a pharmacological drug that at high concentrations can disrupt the integrity of the ER network [ 79 , 80 ], on the structural integrity of the ER network in N . benthamiana leaves expressing mCherry-HDEL.…”
Section: Resultsmentioning
confidence: 99%
“…Tospovirus NSm is predominantly membrane associated [ 49 , 51 , 58 ]. The VRC of Fig mosaic virus , another multipartite negative-strand plant RNA virus, was also found to traffic intracellularly along the ER and actin microfilaments [ 80 ]; however, little has been known about the mechanism of intercellular movement of multipartite negative-strand RNA plant viruses. Our findings have important new implications to guide future mechanistic studies on intercellular trafficking of tospoviruses and other multipartite negative-strand plant RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the macromolecular trafficking of the virus particles of FMV, employing live imaging and ultrastructural analysis, have revealed that the agglomerates of the N protein are passively dragged by the actomyosin‐mediated streaming of the ER, resulting in their rapid movement in plant cells (Ishikawa et al . , ). In virus‐infected cells, the N protein agglomerates are surrounded by ER membranes, which may indicate that they form the basis of enveloped virus particles (Ishikawa et al .…”
Section: Ppsmv Genome Organization Gene Function and Taxonomymentioning
confidence: 89%
“…In virus‐infected cells, the N protein agglomerates are surrounded by ER membranes, which may indicate that they form the basis of enveloped virus particles (Ishikawa et al . , ). The PPSMV N protein may perform similar functions in viral protein trafficking through the ER.…”
Section: Ppsmv Genome Organization Gene Function and Taxonomymentioning
confidence: 99%
“…We studied intracellular trafficking of a plant RNA virus, fig mosaic virus (FMV), which has enveloped particles similar to animal viruses [ 5 ]. Using confocal scanning laser microscopy (CSLM), we found that the FMV nucleocapsid protein (NP), a major structural protein, forms cytoplasmic agglomerates (hereafter called NP bodies or NBs) that rapidly move along the actin-ER network when ectopically expressed in plant cells.…”
mentioning
confidence: 99%